THE ROLE OF AXIOMATIZATION IN THE PROCESS OF MATHEMATICAL THEORY CONSTRUCTION - S.I. MASALOVA (Advanced Engineering Research)
The article covers one of the formalization forms - axiomatization - and its role in the process of construction of mathematical theory and its foundations (abstract mathematical objects). Axiomatic method is used at the stage of systematization of acquired knowledge and is both the result and the means of mathematical knowledge consolidation.